ARTS & LABOR IN THE AGE OF OCCUPATION. - Schwendener, Martha (Afterimage)
The article discusses the Occupy Wall Street (OWS) movement and its relationship to the present and future of art. The author comments on her own participation in the movement, as well as on the participation of artists. Particular focus is paid to the formation and activities of Arts & Labor, a group of artists and other members of the artistic community that formed part of the movement.